HUBUNGAN CARING PERAWAT TERHADAP PELAKSANAAN KOMUNIKASI SBAR PADA SAAT HAND OVER - Devi Novita Damanik; Mona Hastuti (Universitas Prima Indonesia, 2022)
The gap that occurs at the time of handover of the patient is due to incomplete communication so that it can cause disruption in the continuity of nursing which has the potential to endanger the patient. The implementation of patient handover (handover) basically transfers care information and responsibilities from one nurse to another (between shifts) of nurses so that they can provide safe and quality care. This study aims to determine the relationship between nurse caring on the implementation of SBAR communication during hand over cardiac patients in the cardiovascular inpatient ward at Royal Prima Hospital. The research design is descriptive analytic with a cross-sectional approach. This research was conducted in October 2021. The sample in this study were all 32 nurses who served in the cardiovascular inpatient ward. The results of the chi-square test obtained a value of p <0.002, meaning that there is a relationship between nurse caring on the implementation of SBAR communication during hand over cardiac patients in the cardiovascular inpatient ward. It is hoped that respondents can add insight into nurse caring for the implementation of SBAR communication during hand over of cardiac patients in the cardiovascular inpatient ward.